A new group of compounds derived from 4-, 5-, 6- and 7-aminoindoles with antimicrobial activity - Irina S. Stepanenko; Semen A. Yamashkin; Yuliya A. Kostina; Alyona A. Batarsheva; Mikhail A. Mironov (Belgorod National Research University, 2018)
Introduction. The problem of antibiotic resistance of microorganisms is becoming more urgent in the twenty-first century. Microorganisms possess an evolutionary adaptive capacity. Non-adherence to the basic principles of rational antibiotic therapy leads to menacing consequences. More and more pathogenic microbes are becoming resistant to two or more antibiotics. The search for new compounds with antimicrobial activity is one of the principles for overcoming the antibiotic resistance of microorganisms. Materials and methods. Eighteen test-strains of microorganisms and more than 2000 clinical strains of microorganisms, representating the families Micrococcaceae, Streptococcaceae, Enterobacteriaceae, Moraxellaceae, Pseudomonadaceae, Sphingomonadaceae, Xanthomonadaceae were studied for sensitivity to the compounds derived from 4-, 5-, 6- and 7-aminoindoles. A method of serial dilutions to determine the minimal inhibitory concentration (MIC) of the compounds under study was used in the study, as well as a disc diffusion method. Results and discussion. Sensitivity of the test-strains and of clinical strains of microorganisms to the resulting compounds was studied. The compounds based on substituted 4-, 5-, 6-, 7-aminoindoles showed different activity against the test strains and experimental strains of microorganisms in vitro. It was found that the marked antibacterial activity was exhibited by the compounds containing a trifluoromethyl group. The most significant activity was noted in amides and pyrroloquinolones based on 4-aminoindole, 6-aminoindole and 7-aminoindole.The most effective compounds with laboratory codes 5D, 7D, 39D, S3, HD, 4D showed a pronounced antibacterial activity. Conclusion. Antimicrobial activity of the substituted amides and pyrroloquinolines on the basis of 4-, 5-, 6-, 7-aminoindoles was etermined in our study, as well as the spectra of their action against Gram-positive and Gram-negative microorganisms, which are causative agents of non-specific and certain specific human infectious diseases. Moreover, we evaluated the synthetic potentials of the substituted 4-, 5-, 6-, 7-aminoindoles as the starting compounds for synthesizing a series of indolylamides and pyrroloquinolines. Also, the prospects for targeted synthesis of biologically active compounds based on indole-type aromatic amines were determined.